Konfliktuskezelés és stressz összefüggéseinek vizsgálata a humán tőke aspektusából - Kiszeli Dóra (2019)
When I started to write my thesis I had one purpose and that was to figure out if the leaders and employees are able to handle everyday conflicts at their workplace. If they can, I need to know how they manage it. Conflict management basis on communication, that is why I put it on the first place in my thesis. Maybe for the first sight this topic seems basic, but it cannot be a valuable science without content. I believe, everthing and everyone is possible to evolve and change, so I would like to give information about the key to communcate in the right way. At first, I search on the internet some keywords which connects to my thesis and I was surprised and grateful at the same time. I realized the perfect one way cannot exist for communication and conflicts management. Every person should learn how to do that on master level. That point made me sure, this edge of science is capable to improve all the time. Technology is changing, world is changing and that keep us moving, too. So why would not change our thinking? I separated my thesis for two parts. For catch the line, I worked out the scientifical background as I see. Afterthat, I created my version about to develop communicaton and conflict management. My study made up of two type of methods. Three clients participated in personal interviews from different companies. I insisted to reach more and more people for a realistic picture, so I spread online a survey and gladly got back more than a hundred succesfuly filled out. After this jorney in people’s opinions, I wanted to find the solution. Now I know, there is much more need to be given in wrong conflict managment than communicaton. Everybody behave different and has difficulties in life, but all the ways, which was bringing me round and round finished in stress. Stress is a phenomenon our lives and we accepted, but I would like to suggest to try to reduce stress at workplace. I suppose, the solution is in the flexible working hours and conflict management trainings.